Why don’t they want to donate? Cultural and psychological factors influencing the organ donation intention among Hong Kong University students - Wanming Liang; Chi-Shing Tse (PLoS ONE, 2025)
Despite significant advances in transplantation technologies, the global gap between organ availability and demand continues to widen. Hong Kong, in particular, reports notably low organ donation rates among developed regions. Understanding the psychological barriers to donation is essential for developing effective interventions, particularly among young adults who represent a crucial demographic for establishing lifelong donation commitments. The present study examined the complex interplay of psychosocial and emotional factors influencing organ donation intentions among Hong Kong university students. A cross-sectional survey was conducted with 280 university students in Hong Kong, using validated instruments to assess multiple psychological constructs: depressive thinking, altruism, death anxiety, self-efficacy, perceived social support, Big Five personality traits, and Buddhist and Karmic beliefs. Hierarchical regression and moderated mediation analyses were performed to identify direct and indirect predictors for organ donation intentions. Results showed that higher death anxiety (β = −.133, p = .036) and stronger Buddhist beliefs emphasizing bodily integrity (β = −.22, p < .001) were associated with lower donation intentions, while greater self-efficacy (β = .22, p < .001) and perceived social support (β = .28, p < .001) positively predicted donation intentions. Notably, dispositional characteristics including altruism, depressive thinking, personality traits, and Karmic beliefs did not directly predict donation intentions. However, depressive thinking exerted an indirect negative effect on donation intentions through elevated death anxiety, and this mediational pathway was stronger among participants with lower self-efficacy (index of moderated mediation = .035, 95% CI [.0002,.0013]). These findings highlight the critical roles of emotional and situational factors, rather than stable personality characteristics, in determining organ donation intentions among Hong Kong university students. Public health interventions aiming to reduce death anxiety and strengthen self-efficacy may be particularly effective in promoting organ donor registration among young adults in Hong Kong. Future initiatives should prioritize culturally sensitive approaches that address existential concerns while building confidence in donation decision-making.